Understanding Precipitation Moisture Sources and Their Dominant Factors During Droughts in the Vietnamese Mekong Delta - Keke Zhou; Xiaogang Shi (Water Resources Research)
Abstract The Vietnamese Mekong Delta (VMD) is the most productive region in Vietnam in terms of agriculture and aquaculture. Unsurprisingly, droughts have been a prevalent concern for stakeholders across the VMD over the past decades. However, the VMD precipitation moisture sources and their dominant factors during drought conditions were not well understood. Using the ERA5 reanalysis data as inputs, the Water Accounting Model‐2layers (WAM‐2layers), a moisture tracking tool, was applied to identify the VMD precipitation moisture sources from 1980 to 2020. The modeling simulation indicates that the moisture sources transported from the upwind regions dominate the VMD precipitation by 60.4%–93.3%, and the moisture source areas vary seasonally with different monsoon types. Results of the causal inference algorithms indicate that the humidity and wind speed in the upwind area are the dominant factors for driving moisture transport and determining the amount of VMD precipitation in dry and wet seasons, respectively. The local atmospheric conditions may also have a causal effect on moisture recycling. During the drought events in 2015–2016 and 2019–2020, the reduced moisture transport in the 2016 dry season was mainly caused by the anomalies in both humidity and wind speed, while the below average moisture sources in the 2020 dry season were dominated by humidity. In the 2019 wet season, an anomaly in wind speed led to a decrease in the tracked moisture. These findings are of great significance for understanding the moisture sources of precipitation and further improving drought prediction in the VMD.